2019
DOI: 10.1515/glot-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

Dative Alternation in Nigerian English: A Corpus-based Approach

Abstract: Dative alternation is that sort of construction which requires a choice from two available choices; the double object (DOC) (i. e. Please give Mary the book) and the preposition construction (TOC) (i. e. Please give the book to Mary). Empirical evidence detailing the characteristics and motivations of dative choices in different varieties have been put forward in the literature. Albeit, nothing is known about the nature and motivations of this phenomenon in Nigerian variety of English, an important source of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Owolabi, 2012;Umar, 2018), morphosyntactic (e.g. Werner & Fuchs, 2017;Akinlotan & Akande, 2020), and discourse-pragmatic (e.g. Fuchs, Gut & Soneye, 2013;Unuabonah, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Owolabi, 2012;Umar, 2018), morphosyntactic (e.g. Werner & Fuchs, 2017;Akinlotan & Akande, 2020), and discourse-pragmatic (e.g. Fuchs, Gut & Soneye, 2013;Unuabonah, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have described the phonological attributes (Akinjobi, 2009; Akinola, 2019; Gut, 2005; Gut & Fuchs, 2017), lexico‐semantic features (Adegbija, 2003; Alabi, 2000; Jowitt, 2019; Wolf & Igboanusi, 2003), morphosyntactic properties (Akinlotan & Akande, 2020; Akinlotan & Housen, 2017; Fuchs, 2016; Werner & Fuchs, 2017), and discourse‐pragmatic elements (Adegbija & Bello, 2001; Adeyemi, 2017; Fuchs, Gut, & Soneye, 2013; Ogoanah, 2011) of NigE. Some of these studies have revealed the impact of indigenous Nigerian languages and cultures on NigE at various linguistic levels (see also Bamiro, 1994; Jowitt, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This paper focuses on the Standard variety which has been adjudged by scholars (Adegbite, Udofot, & Ayoola, 2014) as being socially acceptable and internationally intelligible. Past studies have described the phonological attributes (Akinjobi, 2009;Akinola, 2019;Gut, 2005;Gut & Fuchs, 2017), lexico-semantic features (Adegbija, 2003;Alabi, 2000;Jowitt, 2019;Wolf & Igboanusi, 2003), morphosyntactic properties (Akinlotan & Akande, 2020;Akinlotan & Housen, 2017;Fuchs, 2016;Werner & Fuchs, 2017), and discoursepragmatic elements (Adegbija & Bello, 2001;Adeyemi, 2017;Fuchs, Gut, & Soneye, 2013;Ogoanah, 2011) of NigE.…”
Section: Introductionmentioning
confidence: 99%